2015
DOI: 10.1002/2014ja020879
|View full text |Cite
|
Sign up to set email alerts
|

Detection of ionospheric disturbances driven by the 2014 Chile tsunami using GPS total electron content in New Zealand

Abstract: A tsunami propagating in open ocean can produce gravity waves and thus perturb the ionosphere.In this study, we employ a second-order numerical difference method using GPS total electron content observed in New Zealand to detect the ionospheric disturbances triggered by the Chile tsunami that occurred on 1 April 2014. We observe traveling ionospheric disturbances (TIDs), which have similar horizontal velocity and direction as the tsunami waves, at different times after the event. According to the arrival times… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…For all these events, the IGW propagation speed and direction were consistent with those of the tsunami, and the TEC perturbation and tsunami height had a similar waveform, with a consistent delay between the two signals (±13 min). A similar TEC signal was later detected in the case of the tsunami triggered by the M w = 9.0 Tohoku event in 2011 (Galvan et al, ; Kherani et al, ; Rolland, Lognonné, Astafyeva, et al, ), including from TEC radio occultation performed by COSMIC (Coïsson et al, ), and by the more recent 2012 Haida Gwaii tsunami (Grawe & Makela, ; Savastano et al, ), the Chilean event of 2014 (Zhang & Tang, ) and the 2015 Illapel tsunami (Grawe & Makela, ).…”
Section: Introductionmentioning
confidence: 63%
“…For all these events, the IGW propagation speed and direction were consistent with those of the tsunami, and the TEC perturbation and tsunami height had a similar waveform, with a consistent delay between the two signals (±13 min). A similar TEC signal was later detected in the case of the tsunami triggered by the M w = 9.0 Tohoku event in 2011 (Galvan et al, ; Kherani et al, ; Rolland, Lognonné, Astafyeva, et al, ), including from TEC radio occultation performed by COSMIC (Coïsson et al, ), and by the more recent 2012 Haida Gwaii tsunami (Grawe & Makela, ; Savastano et al, ), the Chilean event of 2014 (Zhang & Tang, ) and the 2015 Illapel tsunami (Grawe & Makela, ).…”
Section: Introductionmentioning
confidence: 63%
“…These observations have found that (1) tsunamis with sufficiently large open surface displacements generate identifiable TEC perturbations (Galvan et al, ). (2) The TEC perturbations travel at a similar speed and direction with the tsunamis (Galvan et al, ; Rolland et al, ; Zhang & Tang, ). The speed of most tsunami‐induced TEC perturbations is between 200 and 300 m/s (Galvan et al, ; Tang et al, ).…”
Section: Summary Of Major Observational Resultsmentioning
confidence: 99%
“…Distinct TEC signatures due to the tsunami are visible, and the magnitude reached 0.2 TECU (Galvan et al, ). (3) The arrival time of TEC perturbations can be coherent with the arrival time of a tsunami (Rolland et al, ; Zhang & Tang, ), but it can also be earlier than the arrival time of the tsunami that is possibly due the wave dissipation process (Bagiya, Kherani, et al, ). (4) Although tsunamis ceased at costal lines, their signatures in the upper atmosphere can continuously propagate for more than 1,500 km inland (Crowley et al, ).…”
Section: Summary Of Major Observational Resultsmentioning
confidence: 99%
“…The ionospheric TEC series was calculated by the geometry-free combination of dual-frequency GNSS carrier phases for each satellite-receiver pair [27]. The cut-off elevation angle was set as 20 • for each satellite-receiver pair.…”
Section: Methodsmentioning
confidence: 99%